Formulário do perfil psicossocial do paciente anoftálmico com indicação de prótese ocular - Nicodemo, Denise [UNESP]; Ferreira, Lydia Masako (FapUNIFESP (SciELO), 2006)
The patient with anophthalmia may present feelings of inferiority and rejection. Knowing his/her needs and expectations contribute to a better technical intervention. Purpose: To elaborate a questionnaire of the psychosocial profile of the patient with anophthalmia with indication of ocular prosthesis. Methods: An exploratory research was used to elaborate the questionnaire, by means of a guided interview followed by writing down what was said by the interviewees, who were adult patients of the Bucco-Maxillo-Facial Prosthesis Center of FOSJC - UNESP. The guided interview was made up of 14 items directly related to the future outline of the profile. Each item of the interview resulted in questions of the questionnaire, which was pretested twice before reaching its final version. Results: The patients reported, in the exploratory research, unpleasant feelings with the loss of the eye; relationship shyness; expectations regarding surgery and prosthesis use; a wish to receive explanations and to hold their opinion about the treatment. The questionnaire of the psychosocial profile of the patient with anophthalmia with indication of ocular prosthesis is, therefore, made of 43 questions divided into 5 blocks in order to aid the comprehension of the inquired aspects and to facilitate both the computation of data and discussion, and also to improve the selection of questions according to the objective of the researcher or professional. Conclusions: It was concluded that the questionnaire was viable, can be used in full or by selecting blocks and provide a panorama of the patient's history related to the problem he/she faces, from the loss of the ocular globe to the confection of the prosthesis.
Questionnaire of the psychosocial profile of the patient with anophthalmia with indication of ocular prosthesis
Keywords: Anophthalmos; Artificial eye; Artificial/psychology; Psychosocial impact; Quality of life; Questionnaires; adult; anophthalmia; clinical article; controlled study; female; human; interview; lens implant; male; questionnaire; social behavior; social psychology; treatment indication; Adult; Eye, Artificial; Female; Humans; Male; Quality of Life